Advances in Nonprecious Metal Homogeneously Catalyzed Formic Acid Dehydrogenation - Iglesias, Manuel; Fernández-Alvarez, Francisco J. (Catalysts, 2021)
Formic acid (FA) possesses a high volumetric concentration of H2 (53 g L−1). Moreover, it can be easily prepared, stored, and transported. Therefore, FA stands out as a potential liquid organic hydrogen carrier (LOHC), which allows storage and transportation of hydrogen in a safe way. The dehydrogenation to produce H2 and CO2 competes with its dehydration to give CO and H2O. For this reason, research on selective catalytic FA dehydrogenation has gained attention in recent years. Several examples of highly active homogenous catalysts based on precious metals effective for the selective dehydrogenation of FA have been reported. Among them are the binuclear iridium-bipyridine catalysts described by Fujita and Himeda et al. (TOF = 228,000 h−1) and the cationic species [IrClCp*(2,2′-bi-2-imidazoline)]Cl (TOF = 487,500 h−1). However, examples of catalytic systems effective for the solventless dehydrogenation of FA, which is of great interest since it allows to reduce the reaction volume and avoids the use of organic solvents that could damage the fuel cell, are scarce. In this context, the development of transition metal catalysts based on cheap and easily available nonprecious metals is a subject of great interest. This work contains a summary on the state of the art of catalytic dehydrogenation of FA in homogeneous phase, together with an account of the catalytic systems based on non-precious metals so far reported.